Jewish and Christian self-definition ;,v.2 - Baumgarten, Albert I.; Mendelson, Alan; Sanders, Ed Parish, 1937- (London, UK SCM, 1981)
Contents : v. 2 : Aspects of Judaism in the Graeco-Roman period. Includes bibliographical references and indexes.
Keywords: Judaism -- history -- Talmudic period, 10-425. -- addresses, essays, lectures; Church history -- early and primitive church, ca. 30-600 -- addresses, essays, lectures